Randomised trial of perioperative tramadol for canine sterilisation pain management. (5th October 2019) - Meunier, Natascha V; Panti, Ambra; Mazeri, Stella; Fernandes, Karlette A; Handel, Ian G; Bronsvoort, Barend M de C; Gamble, Luke; Mellanby, Richard J
Abstract : Surgical sterilisation to manage free‐roaming dog populations is widely used in many countries. However, few studies have examined optimal postoperative pain management regimens at low‐resource, high‐throughput veterinary clinics. The aim of this study was to examine the efficacy of two intravenous analgesic regimens, preoperative administration of meloxicam and tramadol, or meloxicam alone, in free‐roaming dogs undergoing sterilisation. A total of 125 dogs were included, with 64 dogs in the meloxicam‐tramadol arm and 61 dogs in the meloxicam‐only arm in a non‐inferiority study design. Pain levels in sterilisation surgery patients were assessed at four time points after surgery using the Colorado State University Canine Acute Pain Scale, a Visual Analogue Scale and a modified version of the Glasgow Composite Measure Pain Scale – Short Form. Non‐inferiority was supported for each of the main scoring outcomes using non‐inferiority margins of 0.5, 5 and 0.8, respectively. One dog from the meloxicam‐tramadol group and four dogs in the meloxicam‐only arm required rescue analgesia, with no difference between groups (P=0.21).The study demonstrated that meloxicam was effective in controlling postoperative pain in a high proportion of dogs. The addition of tramadol alongside meloxicam treatment was not found to be of clinical benefit.